The Influence of Employee Performance and Service Quality on Customer Satisfaction of PT Citra Buana Adi In East Jakarta - Yuniarso, Yudi Budi; Estiningsih, Wening (Economics and Business Journal (ECBIS), 2024)
The aim of the research is to determine the influence of Employee Performance and Service Quality on customer Satisfaction at PT Citra Buana Adi workshop in East Jakarta. The method used was quantitative, through collecting questionnaire data on a sample of 35 respondents. From the results of the multiple linear regression test, there is a constant value of 4.170, a regression value for the employee performance variable of 0.260 and a regression value for the service quality variable of 0.288. This means that all independent variables have a direct influence on variable Y. The results of the calculation of the coefficient of determination show that there is an influence of 54.6%, meaning that Employee Performance and Service Quality have an influence of 54.6%. Meanwhile, the remaining 45.3% was influenced by other variables not included in this research. This proves that there is an influence of Employee Performance and Service Quality on Customer Satisfaction at PT Citra Buana Adi workshop in East Jakarta